Travel and Transport Building
Giant Electric Locomotive - Used in hauling The Milwaukee Road's famous transcontinental train, The Olympian, over the Cascade Moutnains. The Milwaukee Road is electrically operated over the Belt, Rocky, Bitter Root and Cascade mountains - a distance of 656 miles.